Magneto-transport phenomena in metal/SiO2/n(p)-Si hybrid structures - Volkov, N.V.; Tarasov, A.S.; Rautskii, M.V.; Lukyanenko, A.V.; Bondarev, I.A.; Varnakov, S.N.; Ovchinnikov, S.G. (Journal of magnetism and magnetic materials, 2018)
•The magnetoresistance (MR) ratio in ac and dc modes can exceed 106%.•The relative change of photo-voltage in magnetic field can reach 103%.•Maximum MR is observed under optical irradiation and impact ionization regime.•MR is related to surface states energy levels transformation in magnetic field.•MR effects are defined by structure design and experimental conditions. Present review touches upon a subject of magnetotransport phenomena in hybrid structures which consist of ferromagnetic or nonmagnetic metal layer, layer of silicon oxide and silicon substrate with n- or p-type conductivity. Main attention will be paid to a number gigantic magnetotransport effects discovered in the devices fabricated on the base of the M/SiO2/n(p)-Si (M is ferromagnetic or paramagnetic metal) hybrid structures. These effects include bias induced dc magnetoresistance, gigantic magnetoimpedance, dc magnetoresistance induced by an optical irradiation and lateral magneto-photo-voltaic effect. The magnetoresistance ratio in ac and dc modes for some of our devices can exceed 106% in a magnetic field below 1 T. For lateral magneto-photo-voltaic effect, the relative change of photo-voltage in magnetic field can reach 103% at low temperature. Two types of mechanisms are responsible for sensitivity of the transport properties of the silicon based hybrid structures to magnetic field. One is related to transformation of the energy structure of the (donor) acceptor states including states near SiO2/n(p)-Si interface in magnetic field. Other mechanism is caused by the Lorentz force action. The features in behaviour of magnetotransport effects in concrete device depend on composition of the used structure, device topology and experimental conditions (bias voltage, optical radiation and others). Obtained results can be base for design of some electronic devices driven by a magnetic field. They can also provide an enhancement of the functionality for existing sensors.